The scene of culture and consciousness III: The Fall of Man - Gans, Eric Lawrence (2023)
For René Girard on his 100th birthday The Genesis account is distinguished from other creation stories by an intuitive imperative of minimalism, of which the reduction to One God is only the most obvious feature. In Chronicles 675-676, by way of appreciating the sharpness of biblical anthropology from GA’s minimal perspective, I discussed in some...